Error reduction therapy in reducing struggle and grope behaviours in apraxia of speech. - Whiteside SP; Inglis AL; Dyson L; Roper A; Harbottle A; Ryder J; Cowell PE; Varley RA; Whiteside, Sandra P; Inglis, A L; Dyson, Lucy; Roper, Abigail; et al. (Neuropsychological Rehabilitation, 2012)
We report an intervention study focused on the speech production difficulties present in acquired apraxia of speech (AOS). The intervention was a self-administered computer therapy that targeted whole word production and incorporated error reduction strategies. The effectiveness of the therapy was contrasted to that of a visuospatial sham computer program, and performance across treated words, and two sets of matched words, was assessed. Two groups of participants completed the study which employed a two-phase cross-over treatment design. Participants were randomly assigned to a speech first or sham first condition. Treatments were administered for six weeks, with a four week rest between interventions. Participants were assessed five times in total; twice at baseline, once following each of the intervention phases, and once following a lapse of eight weeks after the end of the second phase of intervention. The occurrence of accurate word production and speech characterised by struggle and groping behaviours was recorded on a repetition task. Participants showed significant gains in speech accuracy and fluency, and reductions in articulatory groping and struggle behaviours following the use of the speech program. These gains were largely maintained once the therapy was withdrawn.